An evaluation of the effectiveness of regional bible shools program in pentecostal assemblies of God church in Tanzania - Mwakisole, Agrey Harry (Nairobi : PAC University, 2010)
Includes bibligraphical references
Keywords: Educational Management and Leadership; Teaching Programs -- Quality; Regional Bible Schools -- Pentecostal Assemblies of God Church -- Tanzania